2012
DOI: 10.1007/s10103-012-1190-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy improves the inflammatory profile of rats with heart failure

Abstract: Following heart failure (HF), immune activation leads to an imbalance between pro-inflammatory and anti-inflammatory cytokines. Low-level laser therapy (LLLT) has been used as an anti-inflammatory treatment in several disease conditions. However, the effect of LLLT on the skeletal muscle of rats with HF remains unclear. The present report aimed to evaluate the influence of LLLT on the inflammatory profile of rats with HF. The left coronary artery was ligated to induce HF and a sham operation was performed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…In a recent study, the authors observed that LLLT can modulate the balance between pro and anti-inflammatory cytokines, both systemically and peripherally in lean rats [40]. Other study shows that laser irradiation with wavelength of 808 nm, similar with our study, in coronary artery, results in increase of anti-inflammatory and decrease in the pro-inflammatory interleukins levels [41].…”
Section: Discussionsupporting
confidence: 82%
“…In a recent study, the authors observed that LLLT can modulate the balance between pro and anti-inflammatory cytokines, both systemically and peripherally in lean rats [40]. Other study shows that laser irradiation with wavelength of 808 nm, similar with our study, in coronary artery, results in increase of anti-inflammatory and decrease in the pro-inflammatory interleukins levels [41].…”
Section: Discussionsupporting
confidence: 82%
“…Systemically, our results also indicate no significant difference between Sham and HF rats with respect to the effect of TU on pro-and anti-inflammatory cytokines. Similarly, a recent study from our group reported no difference in plasma TNF-a levels in HF rats (Hentschke et al 2013). However, other studies have reported increases in TNF-a, and IL-6 levels and decreases in IL-10 levels in HF models (Francis et al 2004;Nunes et al 2008;Sugita et al 2008).…”
Section: Discussionmentioning
confidence: 86%
“…Pressure analogue signals were digitalized by a data acquisition system (AT/Codas, Dataq Instruments, Akron, OH, USA) at a sampling rate of 2,000 Hz. These data were used to determine mean arterial pressure (MAP), left ventricular systolic pressure (LVSP), left ventricular maximum change in pressure over time (1dP/dt max ), left ventricular minimum change in pressure over time (-dP/dt min ) and left ventricular enddiastolic pressure (LVEDP) (Hentschke et al 2013;Nunes et al 2008). The last parameter was determined manually by detecting the point of inflection to the end of the diastole via analysis of the ventricular pressure wave.…”
Section: Cardiac Hemodynamic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were maintained at Guedel's anaesthetic level III (Hecker et al, 1983;Colman et al, 2002). Myocardial infarction was induced as previously described (Pfeffer et al, 1979;Hentschke et al, 2013). The thoracotomy was performed at the level of the left fourth intercostal space, the pericardium was cut and the left anterior descending coronary artery was ligated with a 6.0 mono nylon wire.…”
Section: Surgery To Induce Myocardial Infarctionmentioning
confidence: 99%